Type I interferon licenses enhanced innate recognition and transcriptional responses to Franciscella tularensis live vaccine strain. Issue 5 (July 2016) - Richard, Katharina; Vogel, Stefanie N; Perkins, Darren J
The innate inflammatory response to Francisella tularensis ( Ft ) in macrophages is significantly governed by the expression of type I interferon (IFN). Previously, the proteolytic processing and maturation of pro-IL-1β protein was shown to depend upon type I IFN expression. We show in this report that paracrine type I IFN can profoundly enhance innate recognition and TLR-dependent transcriptional responses to Ft infection upstream of its role in inflammasome regulation in both primary human monocyte-derived macrophages and primary murine peritoneal macrophages but not murine bone marrow-derived macrophages. This type I IFN-enhanced response is synergistic with TLR2 transcriptional responses, partially TLR2-independent, but strictly MyD88-dependent.